High-dynamics silicon-based negative electrode aqueous binder, preparation method thereof and battery

By regulating the acrylic system and adding zwitterionic monomers and phenolic ionic liquids, a highly kinetic water-based binder was prepared, which solved the problem of electrode structure failure and cycle performance degradation caused by volume changes in the charge and discharge process of silicon-based negative electrode materials, and achieved high cycle stability and energy density of the battery.

CN119709058APending Publication Date: 2025-03-28TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411773361.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The volume changes of existing silicon-based negative electrode materials during charging and discharging lead to damage to the electrode structure and degradation of cycling performance. The quality problems of the binder directly affect the stability and life of the battery.

Method used

By finely controlling the types of acrylic systems, combining zwitterionic monomers and phenolic ionic liquids, a highly kinetic water-based adhesive is prepared, and the mass proportion of acrylic monomers, acrylic derivative monomers and acrylic ester monomers are optimized to form adhesives with high mechanical strength, flexibility and high adhesion.

Benefits of technology

Effectively alleviate the volume expansion during the circulation of silicon-based negative electrode materials, reduce the swelling rate, and improve the cycle stability and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170801240000181
    Figure BDA0005170801240000181
  • Figure BDA0005170801240000182
    Figure BDA0005170801240000182
  • Figure BDA0005170801240000191
    Figure BDA0005170801240000191
Patent Text Reader

Abstract

The invention provides a high-dynamics silicon-based negative electrode aqueous binder, a preparation method thereof and a battery. In the invention, firstly, an acrylic acid system is finely researched, and three different acrylic acid system monomers are selected; by optimizing the variety and proportion of the components, the balance between the mechanical strength and the flexibility is achieved, and meanwhile, the advantages of high viscosity and high stability are achieved; on the second aspect, the zwitterionic monomer with ion conduction performance and the phenol ionic liquid are also added, so that the ion transmission performance is improved; and the aqueous binder with high dynamics is obtained. The high-dynamics aqueous binder can effectively relieve the problem of volume expansion of a silicon-based negative electrode material in a battery; the swelling rate is reduced, high viscosity and flexibility are achieved at the same time, and the cycle stability of the material can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a high-kinetic silicon-based negative electrode aqueous binder, a preparation method thereof, and a battery. Background Art

[0002] In recent years, with the increasingly severe energy crisis and environmental pollution problems, the development of new energy technologies has received widespread attention worldwide. Among the many new energy technologies, lithium-ion batteries have become a hot spot for research and application due to their advantages such as high energy density, long life and no memory effect. However, traditional graphite anode materials have approached the limit of their theoretical capacity and cannot meet the growing demand for high energy density. Therefore, silicon-based anode materials have become an ideal choice to replace graphite due to their high theoretical specific capacity (about 4200mAh / g, more than ten times that of graphite). However, silicon-based anode materials undergo significant volume changes during the charge and discharge process, which leads to the destruction of the electrode structure and the decline of cycle performance; among them, the quality of the binder is directly related to the stability and life of the battery during the cycle process, and has become one of the key factors restricting the performance improvement of silicon-based batteries.

[0003] In the manufacturing process of silicon-based batteries, the main function of the binder is to tightly bind silicon particles with conductive agents, current collectors, etc. to form a stable electrode structure. If the quality of the binder is poor, it will not only cause the electrode structure to peel off during the charge and discharge process, but also seriously affect the cycle performance and service life of the battery. In the prior art, the commonly used silicon-based negative electrode binders are mainly CMC (carboxymethyl cellulose), PAA (polyacrylic acid), PVDF (polyvinylidene fluoride) and other types.

[0004] Among them, PVDF, as a common binder material, has a relatively simple molecular chain structure and good flexibility, so it can adapt to the volume expansion of silicon particles during the charging and discharging process to a certain extent. However, due to the weak interaction between PVDF and silicon particles, when the volume of silicon particles expands significantly, the PVDF binder is easily destroyed, resulting in instability of the electrode structure, which in turn affects the cycle performance of the battery. CMC, as another commonly used water-based binder, has good swelling performance and capacity retention in the electrolyte. However, due to the rigid six-membered heterocyclic structure contained in its molecular chain, the flexibility of CMC is relatively poor. During the charging and discharging process of the battery, this rigid structure easily causes the electrode sheet to crack, thereby affecting the cycle stability of the battery. The acrylic binder PAA helps to maintain the structural stability of the electrode sheet in the electrolyte due to its small swelling effect, thereby improving the electrochemical performance of the battery; however, PAA is more brittle, the polymer chain is relatively fragile, and it is easy to break during the charging and discharging process of the battery; once subjected to external force, the PAA binder is also prone to permanent deformation, resulting in agglomeration of the active material, thereby affecting the capacity of the active material. This will not only reduce the rate performance of the battery, but also have an adverse effect on the cycle stability of the battery.

[0005] Therefore, it is of great significance to develop an adhesive with both excellent dynamics and high bonding strength. Summary of the invention

[0006] The present invention aims at the problems in the prior art and discloses a high-kinetic silicon-based negative electrode aqueous binder and a preparation method thereof and a battery. By finely regulating the types of acrylic acid systems and matching zwitterionic monomers and phenolic ionic liquids, a high-kinetic aqueous binder with high viscosity and flexibility is prepared within an appropriate mass ratio range, which is conducive to solving the problems of volume expansion of silicon-based negative electrode materials during the cycle, high brittleness of the binder, and easy breakage.

[0007] The present invention is achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a high-kinetic silicon-based negative electrode aqueous binder; wherein the raw materials of the aqueous binder include five parts:

[0009] By weight,

[0010] 20-35 parts of acrylic monomer;

[0011] 15 to 30 parts of acrylic acid derivative monomer;

[0012] 8 to 18 parts of acrylic ester monomer;

[0013] 5 to 15 parts of zwitterionic monomer;

[0014] 4 to 10 parts of phenolic ionic liquid;

[0015] Wherein, the acrylic acid derivative monomer has a nitrogen-containing hydrogen bond acceptor derivative group.

[0016] As a further solution, the raw materials of the high-kinetic silicon-based negative electrode aqueous binder also include, by weight, 0.5-1 parts of initiator and 200-450 parts of water solvent.

[0017] As a further embodiment, the acrylic monomer includes one or more of acrylic acid, alkyl acrylic acid, acrylate, and alkyl acrylate;

[0018] Furthermore, the salts of the acrylate and alkyl acrylate can be selected from lithium salt, sodium salt and potassium salt;

[0019] Furthermore, the alkyl group is selected from one or more of methyl, ethyl and propyl.

[0020] As a further solution, the acrylic acid derivative monomer is selected from acrylamide monomers and acrylonitrile monomers; wherein the mass ratio of acrylamide monomers to acrylonitrile monomers is in the range of 1:(0.5-1.5).

[0021] As a further embodiment, the acrylamide monomers include one or more of acrylamide, methacrylamide, N-methylacrylamide, N-ethylacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, N-hydroxypropylacrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide.

[0022] As a further embodiment, the acrylonitrile monomer includes one or more of acrylonitrile, α-methacrylonitrile, and α-ethylacrylonitrile.

[0023] As a further embodiment, the acrylic ester monomer includes one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, lauryl acrylate, vinyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate.

[0024] As a further embodiment, the zwitterionic monomer includes one or more zwitterionic organic acid ester ionic monomers selected from 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate; one or more zwitterionic organic salt ionic monomers selected from 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-[bis[2-(methacryloyloxy)ethyl](methyl)ammonium]-1-propane sulfonate, (3-(methacryloylamino)propyl)dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 3-[[2-(acryloyloxy)ethyl]dimethylammonium]propane-1-sulfonate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonium]butane-1-sulfonate, and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate.

[0025] As a further embodiment, the zwitterionic monomer is preferably selected from zwitterionic organic acid ester ionic monomers.

[0026] As a further solution, the phenolic ionic liquid is a product obtained by acid-base neutralization reaction of phenolic acidic components and alkaline components; the mass ratio of the phenolic acidic components to the alkaline components is selected from 1: (0.7-1.5).

[0027] As a further embodiment, the phenolic acidic components include one or more of gallic acid, protocatechuic acid, vanillic acid, syringic acid, gentisic acid, caffeic acid, ferulic acid, p-coumaric acid, sinapic acid, rosmarinic acid, p-hydroxybenzoic acid and salicylic acid; the alkaline components include one or more of choline, betaine, ethylenediamine and triethylamine.

[0028] Preferably, the phenolic acidic component is preferably selected from phenolic acidic components having a substituent group (-C=C-CO-) connected to a carbon-carbon unsaturated bond on the carbonyl carbon; including one or more of caffeic acid, ferulic acid, sinapinic acid, and rosmarinic acid;

[0029] Preferably, the alkaline component is selected from alkaline components containing quaternary ammonium groups, including one or more of choline and betaine.

[0030] As a further solution, the raw materials of the high-kinetic silicon-based negative electrode aqueous binder are preferably: 25 to 35 parts of acrylic monomers;

[0031] 15 to 23 parts of acrylic acid derivative monomer;

[0032] 10 to 13 parts of acrylic ester monomer;

[0033] 7 to 10 parts of zwitterionic monomer;

[0034] 4 to 7 parts of phenolic ionic liquid;

[0035] Wherein, the acrylic acid derivative monomer has a nitrogen-containing hydrogen bond acceptor derivative group.

[0036] Furthermore, the nitrogen-containing hydrogen bond acceptor derivative group includes one or more of an amino group, an amide group, a carbon-nitrogen double bond (C=N), and a carbon-nitrogen triple bond (C≡N).

[0037] Furthermore, the raw materials of the water-based binder are preferably acrylic acid monomers, acrylamide monomers, acrylonitrile monomers, acrylic ester monomers, amphoteric organic acid ester ion monomers, and phenolic ionic liquids.

[0038] In a second aspect, the present invention provides a method for preparing a high-kinetic silicon-based negative electrode aqueous binder; the preparation method is used to prepare the high-kinetic silicon-based negative electrode aqueous binder described in the first aspect; the steps include:

[0039] S1: heating the acrylic acid monomer, acrylic acid derivative monomer, alkaline solution and aqueous solution to 50-80° C. under an inert atmosphere; keeping the temperature for 15-35 minutes;

[0040] S2: Adding acrylic acid derivative monomer to S1 again; adding initiator and keeping warm for 2-4 hours to obtain the first slurry; adjusting the temperature range to 65-90°C;

[0041] S3: When the temperature reaches the temperature range of 65-90° C. described in S2, a mixture of acrylic acid monomers, acrylic acid derivative monomers, acrylic ester monomers, zwitterionic monomers, and phenolic ionic liquids is added to the first slurry described in S2; after the addition is completed, the temperature is kept for 7-13 hours to obtain a second slurry;

[0042] S4: Add a strong alkaline aqueous solution to the second slurry in S3; adjust the pH value to 7-8; and dilute with water to obtain a high-kinetic silicon-based negative electrode aqueous binder.

[0043] As a further solution, the acrylic acid derivative monomer in S1 is preferably selected from acrylamide monomers; the acrylic acid derivative monomer in S2 is preferably selected from acrylonitrile monomers; the acrylic acid derivative monomer in S3 is preferably selected from acrylamide monomers and acrylonitrile monomers; wherein the acrylic acid derivative monomer has a nitrogen-containing hydrogen bond acceptor derivative group.

[0044] As a further solution, the solid content of the high-kinetic silicon-based negative electrode aqueous binder is in the range of 10-30%. The solid content of the high-kinetic silicon-based negative electrode aqueous binder refers to the ratio of the mass of the solid component in the prepared aqueous binder to the total mass of the aqueous binder.

[0045] As a further embodiment, the adding rate in S3 ranges from 3 to 6 seconds per drop.

[0046] As a further scheme, the initiator in S2 is selected from one or more of inorganic peroxide initiators, organic peroxide initiators, and azo initiators; as some specific examples: the inorganic peroxide initiator is selected from one or more of ammonium persulfate, potassium persulfate, and sodium persulfate; the organic peroxide initiator is selected from one or more of benzoyl peroxide, di-tert-butyl peroxide, and methyl ethyl ketone peroxide; the azo initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate.

[0047] As a further solution, the inert atmosphere in S1 is selected from one or more of a nitrogen atmosphere and a helium atmosphere.

[0048] As a further solution, the atmosphere flow rate of the inert atmosphere in S1 is selected from 500-1000 mL / min.

[0049] As a further solution, the type of the alkaline solution in S1 is selected from one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide; and the concentration of the alkaline solution is in the range of 1-10%.

[0050] As a further solution, in S4, the strong alkali aqueous solution is selected from one or more of a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, and a lithium hydroxide aqueous solution; and the concentration of the strong alkali aqueous solution is in the range of 10-20%.

[0051] As a further solution, the preparation method of the phenolic ionic liquid in S3 includes: adding phenolic acidic components and alkaline components into a solvent according to a mass ratio; after the reaction is completed under an inert atmosphere, removing the solvent to obtain the phenolic ionic liquid.

[0052] Furthermore, the reaction time is selected from 1-3h.

[0053] As a further embodiment, the solvent is selected from one or more solvents of methanol, ethanol, isopropanol, ethyl acetate, and ethylene dichloride.

[0054] In a third aspect, the present invention provides a silicon-based negative electrode sheet, which includes the high-kinetic silicon-based negative electrode aqueous binder, a conductive agent, and a silicon-based active material described in the first aspect.

[0055] Furthermore, the silicon-based active material includes silicon granular materials, silicon-oxygen composite materials, and silicon-carbon composite materials; as some specific examples: the silicon-oxygen composite materials include one or more of silicon monoxide and silicon dioxide; the silicon-carbon composite materials include one or more of silicon / graphite composite materials, silicon / carbon nanotube composite materials, and silicon / graphene composite materials.

[0056] In a third aspect, the present invention provides a battery, comprising the silicon-based negative electrode sheet, positive electrode sheet, separator, and electrolyte described in the third aspect.

[0057] The characteristics and beneficial effects of the present invention are:

[0058] The present invention firstly makes full use of the characteristics of acrylic binder system with high adhesion, low swelling and compatibility to prepare a more environmentally friendly water-based binder. At the same time, the present invention also finely optimizes and regulates the acrylic system, adopts acrylic monomers, acrylic derivative monomers and propylene ester monomers, exerts their mutual synergistic effects, and controls their mass proportion to achieve a balance of mechanical strength, flexibility and high adhesion, effectively alleviates the volume expansion of silicon-based negative electrode materials during the cycle, and has a low swelling rate. At the same time, the present invention also adds zwitterionic monomers with good interface compatibility with the acrylic system and phenolic ionic liquids with high ionic conductivity; it can improve the problem of low ionic conductivity of the acrylic system, thereby preparing a water-based binder with high dynamic performance, high flexibility and bonding performance; it effectively improves the problem of large brittleness and easy breakage of the binder in the prior art, which affects the battery energy density and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0060] Figure 1 This is a SEM image of an electrode sheet obtained by applying the binder prepared in Example 1 of the present invention to a silicon-based negative electrode;

[0061] Figure 2 This is a SEM image of an electrode sheet prepared by applying the binder prepared in Comparative Example 1 of the present invention to a silicon-based negative electrode. DETAILED DESCRIPTION

[0062] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.

[0063] In a first aspect, the present invention provides a high-kinetic silicon-based negative electrode aqueous binder; wherein the raw materials of the aqueous binder include five parts:

[0064] By weight,

[0065] 20-35 parts of acrylic monomer;

[0066] 15 to 30 parts of acrylic acid derivative monomer;

[0067] 8 to 18 parts of acrylic ester monomer;

[0068] 5 to 15 parts of zwitterionic monomer;

[0069] 4 to 10 parts of phenolic ionic liquid;

[0070] Wherein, the acrylic acid derivative monomer has a nitrogen-containing hydrogen bond acceptor derivative group.

[0071] The nitrogen-containing hydrogen bond acceptor derivative group usually has a strong electronegativity, thereby bringing a higher reactivity, and the introduced nitrogen atom has a naked lone pair of electrons, which brings a suitable hydrogen bonding strength in the acrylic acid system. As some illustrative examples: the nitrogen-containing hydrogen bond acceptor derivative group includes one or more of an amino group, an amide group, a carbon-nitrogen double bond (C=N), and a carbon-nitrogen triple bond (C≡N).

[0072] In view of the high adhesion, low swelling and compatibility of acrylic binder systems, they have better adaptability in the preparation of environmentally friendly water-based binders; this application relates to an acrylic system water-based binder, and the compounding and proportion of its components are studied and optimized, aiming to improve its brittleness, easy breakage, unstable cycle and other problems in battery applications. In the first aspect of this application, a detailed study of the acrylic system was conducted, and three different acrylic system monomers were selected; they are acrylic monomers, acrylic derivative monomers and acrylic ester monomers.

[0073] First, acrylic monomers contain a large number of carboxyl groups, which can form strong hydrogen bonds with the surface of active materials, thus having high bonding performance. At the same time, they have good electrochemical stability and low electrolyte swelling, and have outstanding performance in improving battery performance. However, the molecular chain of acrylic monomers is relatively rigid, and it is easy to undergo permanent deformation after being subjected to force, which may cause the active material to agglomerate. Its water resistance and solvent resistance are insufficient, which may affect the stability of the battery. Therefore, we also added acrylic derivative monomers, which have higher activity through the presence of hydrogen bond receptor groups introduced by them, enhance the interaction with active materials, and reduce the mobility of polymer chain segments by establishing a multiple hydrogen bond supramolecular cross-linked network between polymer chains, thereby improving the bonding performance and preparing a complex three-dimensional network. At the same time, its multiple hydrogen bond supramolecular structure is thermally reversible, which can provide self-healing ability for the polymer, which is beneficial to reduce the permanent deformation of acrylic monomers under force. In addition, acrylic derivative monomers have longer alkyl chains, which help to improve the water resistance and solvent resistance of olefin monomers; improve the performance of preparing water-based adhesives. However, acrylic monomers and acrylic derivative monomers have strong hydrogen bonding, which can easily lead to insufficient flexibility of the binder cross-linking network due to excessive hydrogen bonding, which is not conducive to bearing the stress generated by the volume expansion of silicon-based negative electrode materials during battery cycling, reducing their low swelling effect; therefore, we also selected acrylate monomers that are compatible with the acrylic system. Acrylic ester monomers not only have good water resistance and alcohol resistance, improve the performance of water-based binders, and prevent side reactions of binders, but also balance the problem of insufficient flexibility caused by excessive hydrogen bonding, further improve the flexibility of the binder's three-dimensional network structure, and inhibit the volume expansion of silicon-based negative electrode materials; prevent the binder from being too brittle and causing breakage and falling off; and make the prepared binder have higher cycle stability and safety.

[0074] On the second hand, although the acrylic system binder has good chemical stability and mechanical stability; it can effectively inhibit swelling in the silicon-based negative electrode system and improve the bonding performance; but its ion transport performance may not be as good as other types of binders; for this reason, the present application also adds zwitterionic monomers and phenolic ionic liquids with ion-conducting properties to obtain a water-based binder with high kinetics. Zwitterionic monomers have anionic and cationic groups, which can form a strong interaction with the acrylic system, enhancing the interfacial compatibility between the acrylic systems; and through the regulation of anions and cations, the shortcomings of the acrylic system in ion transport performance can be improved; and the addition of zwitterionic monomers can improve the mechanical strength of the binder. This improvement in mechanical strength helps to resist the stress caused by the volume expansion of the silicon-based negative electrode and reduce the possibility of fracture. In addition, in order to further enhance the ionic conductivity of the water-based binder, the present application also uses a phenolic ionic liquid, which is prepared by classifying the reaction of acidic components and alkaline components, and also has anions and cations, and has good compatibility with zwitterionic monomers, and then has good interfacial stability with the acrylic system, forming a more uniform water-based binder system. The intermolecular lubricating effect of phenolic ionic liquids can reduce the friction between the polymer chains formed by the polymerization of the above-mentioned monomers and increase the flexibility of the binder, so that the binder can better absorb stress changes and balance swelling when the silicon-based negative electrode participates in the cycle; and the phenolic ionic liquids themselves have high ionic conductivity, and can also improve the dispersibility of ionic liquids in acrylic system binders, forming a uniform ion distribution, which is beneficial to assist the aqueous binder to have better ion conductivity; at the same time, the carboxyl group in the acrylic system can form hydrogen bonds with the hydroxyl group in the phenolic ionic liquid; this hydrogen bond has a strong intermolecular interaction and can effectively bind the phenolic ionic liquid in the acrylic system; it is crucial for balancing the mechanical properties, flexibility and electrochemical stability of the aqueous binder.

[0075] As a further solution, the raw materials of the high-kinetic silicon-based negative electrode aqueous binder also include, by weight, 0.5-1 parts of initiator and 200-450 parts of water solvent.

[0076] As a further embodiment, the acrylic monomer includes one or more of acrylic acid, alkyl acrylic acid, acrylate, and alkyl acrylate;

[0077] Furthermore, the salts of the acrylate and alkyl acrylate can be selected from lithium salt, sodium salt and potassium salt;

[0078] Furthermore, the alkyl group is selected from one or more of methyl, ethyl and propyl.

[0079] Selecting a smaller alkyl chain (methyl, ethyl, propyl) can further balance the flexibility and rigidity of acrylics; it is beneficial to improve the high swelling rate and brittleness during cycling in a silicon-based negative electrode system.

[0080] As a further solution, the acrylic acid derivative monomer is selected from acrylamide monomers and acrylonitrile monomers; wherein the mass ratio of acrylamide monomers to acrylonitrile monomers is in the range of 1:(0.5-1.5).

[0081] Both acrylamide and acrylonitrile have high reactivity. The nitrogen atom in the amide structure has a lone pair of electrons. When reacting with the acrylate group and the carboxyl group of acrylic acid, it can form more cross-linking sites, improve the mechanical strength and cohesion of the prepared binder; at the same time, it enhances the bonding force with the active substance; at the same time, the nitrogen atom contained in it produces a covalent bond with the benzene ring of the phenolic acid structure, and has a strong connection ability. Nitrile compounds will produce free radicals during polymerization and grow into polymer chains, which can not only construct a complex network structure, but also further enhance its flexibility; promote the formation of high-dynamic, high-viscosity silicon-based negative electrode aqueous binder.

[0082] As a further embodiment, the acrylamide monomers include one or more of acrylamide, methacrylamide, N-methylacrylamide, N-ethylacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, N-hydroxypropylacrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide.

[0083] As a further embodiment, the acrylonitrile monomer includes one or more of acrylonitrile, α-methacrylonitrile, and α-ethylacrylonitrile.

[0084] As a further embodiment, the acrylic ester monomer includes one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, lauryl acrylate, vinyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate.

[0085] As a further embodiment, the zwitterionic monomer includes one or more zwitterionic organic acid ester ionic monomers selected from 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate; one or more zwitterionic organic salt ionic monomers selected from 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-[bis[2-(methacryloyloxy)ethyl](methyl)ammonium]-1-propane sulfonate, (3-(methacryloylamino)propyl)dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 3-[[2-(acryloyloxy)ethyl]dimethylammonium]propane-1-sulfonate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonium]butane-1-sulfonate, and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate.

[0086] As a further solution, the zwitterionic monomer is preferably selected from zwitterionic organic acid ester ionic monomers; this type of ionic liquid also includes an ester group, which can further balance the flexibility of the system; at the same time, the zwitterionic monomer containing an ester group has further chemical stability, which is beneficial to improving the electrochemical stability of the aqueous binder.

[0087] As a further solution, the phenolic ionic liquid is a product obtained by acid-base neutralization reaction of phenolic acidic components and alkaline components; the mass ratio of the phenolic acidic components to the alkaline components is selected from 1: (0.7-1.5).

[0088] As a further embodiment, the phenolic acidic components include one or more of gallic acid, protocatechuic acid, vanillic acid, syringic acid, gentisic acid, caffeic acid, ferulic acid, p-coumaric acid, sinapic acid, rosmarinic acid, p-hydroxybenzoic acid and salicylic acid; the alkaline components include one or more of choline, betaine, ethylenediamine and triethylamine.

[0089] In the present application, phenolic acidic substances and phenolic alkaline substances are subjected to a condensation reaction to prepare phenolic ionic liquids, which are applied in the preparation process of aqueous binders to form a composite structure with better ion conductivity, which is beneficial to improving the ion transmission performance of the aqueous binder prepared in the present application; the amide bonds formed by the reaction can also enhance the interaction between polymer chains, improve the mechanical strength and flexibility of the binder, and help resist the stress caused by the volume expansion of the silicon-based negative electrode; condensing phenolic acidic substances and phenolic alkaline substances can also effectively avoid side reactions when the phenolic acidic substances and phenolic alkaline substances are used alone, which is not as stable as forming amide bonds.

[0090] Preferably, the phenolic acidic component is preferably selected from phenolic acidic components having a substituent group (-C=C-CO-) connected to a carbon-carbon unsaturated bond on the carbonyl carbon; including one or more of caffeic acid, ferulic acid, sinapinic acid, and rosmarinic acid;

[0091] Preferably, the alkaline component is selected from alkaline components containing quaternary ammonium groups, including one or more of choline and betaine.

[0092] The preferred phenolic acidic component of the present application also has a special carbon-carbon unsaturated double bond structure; the preferred alkaline component contains a quaternary ammonium structure; when preparing phenolic ionic liquids, the quaternized amide bond can further improve the stability of the binder in the electrolyte, and the carbon-carbon unsaturated double bond structure gives the phenolic acidic component a higher reactivity; it is more conducive to the preparation of stable and highly active phenolic ionic liquids; when cross-linking and polymerizing with zwitterionic monomers and acrylic acid systems, a higher cross-linking density can be formed; and the bonding performance is further enhanced.

[0093] As a further solution, the raw materials of the high-kinetic silicon-based negative electrode aqueous binder are preferably: 25 to 35 parts of acrylic monomers;

[0094] 15 to 23 parts of acrylic acid derivative monomer;

[0095] 10 to 13 parts of acrylic ester monomer;

[0096] 7 to 10 parts of zwitterionic monomer;

[0097] 4 to 7 parts of phenolic ionic liquid;

[0098] Wherein, the acrylic acid derivative monomer has a nitrogen-containing hydrogen bond acceptor derivative group.

[0099] Furthermore, the raw materials of the water-based binder are preferably acrylic acid monomers, acrylamide monomers, acrylonitrile monomers, acrylic ester monomers, amphoteric organic acid ester ion monomers, and phenolic ionic liquids.

[0100] The types of ingredients within the preferred range are more conducive to balancing the flexibility and high viscosity in the aqueous binder, which is conducive to better inhibiting the swelling of the silicon-based negative electrode material during the cycle and obtaining better ion conductivity; achieving a balance between high kinetics, high viscosity and good flexibility.

[0101] In a second aspect, the present invention provides a method for preparing a high-kinetic silicon-based negative electrode aqueous binder; the preparation method is used to prepare the high-kinetic silicon-based negative electrode aqueous binder described in the first aspect; the steps include:

[0102] S1: heating the acrylic acid monomer, acrylic acid derivative monomer, alkaline solution and aqueous solution to 50-80° C. under an inert atmosphere; keeping the temperature for 15-35 minutes;

[0103] S2: Adding acrylic acid derivative monomer to S1 again; adding initiator and keeping warm for 2-4 hours to obtain the first slurry; adjusting the temperature range to 65-90°C;

[0104] S3: When the temperature reaches the temperature range of 65-90° C. described in S2, a mixture of acrylic acid monomers, acrylic acid derivative monomers, acrylic ester monomers, zwitterionic monomers, and phenolic ionic liquids is added to the first slurry described in S2; after the addition is completed, the temperature is kept for 7-13 hours to obtain a second slurry;

[0105] S4: Add a strong alkaline aqueous solution to the second slurry in S3; adjust the pH value to 7-8; and dilute with water to obtain a high-kinetic silicon-based negative electrode aqueous binder.

[0106] As a further solution, the acrylic acid derivative monomer in S1 is preferably selected from acrylamide monomers; the acrylic acid derivative monomer in S2 is preferably selected from acrylonitrile monomers; the acrylic acid derivative monomer in S3 is preferably selected from acrylamide monomers and acrylonitrile monomers; wherein the acrylic acid derivative monomer has a nitrogen-containing hydrogen bond acceptor derivative group.

[0107] When preparing a high-dynamic water-based binder, the present application firstly polymerizes acrylic monomers and acrylamide monomers in an inert atmosphere; so as to form more cross-linking sites by utilizing the characteristics of amides, and to have a preliminary network structure; and then by adding acrylonitrile monomers, more polymer chains are grown, and while further forming a network structure, a certain flexibility is provided; thus, a preliminary and stable network structure is provided, and this structure provides more cross-linking points for subsequent monomers and compounds, which is conducive to forming a more complex and more stable three-dimensional network structure. Subsequently, under suitable temperature conditions, the monomers of the four components are evenly mixed and added to the first slurry at a certain rate to prepare the high-dynamic water-based binder of the present invention.

[0108] As a further solution, the solid content of the high-kinetic silicon-based negative electrode aqueous binder is in the range of 10-30%. The solid content of the high-kinetic silicon-based negative electrode aqueous binder refers to the ratio of the mass of the solid component in the aqueous binder after preparation to the total mass of the aqueous binder.

[0109] As a further embodiment, the addition rate in S3 ranges from 3 to 6 seconds per drop;

[0110] As a further scheme, the initiator in S2 is selected from one or more of inorganic peroxide initiators, organic peroxide initiators, and azo initiators; as some specific examples: the inorganic peroxide initiator is selected from one or more of ammonium persulfate, potassium persulfate, and sodium persulfate; the organic peroxide initiator is selected from one or more of benzoyl peroxide, di-tert-butyl peroxide, and methyl ethyl ketone peroxide; the azo initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate.

[0111] As a further solution, the inert atmosphere in S1 is selected from one or more of a nitrogen atmosphere and a helium atmosphere.

[0112] As a further solution, the atmosphere flow rate of the inert atmosphere in S1 is selected from 500-1000 mL / min.

[0113] As a further solution, the type of the alkaline solution in S1 is selected from one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide; and the concentration of the alkaline solution is in the range of 1-10%.

[0114] As a further solution, in S4, the strong alkali aqueous solution is selected from one or more of a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, and a lithium hydroxide aqueous solution; and the concentration of the strong alkali aqueous solution is in the range of 10-20%.

[0115] As a further solution, the preparation method of the phenolic ionic liquid in S3 includes: adding phenolic acidic components and alkaline components into a solvent according to a mass ratio; after the reaction is completed under an inert atmosphere, removing the solvent to obtain the phenolic ionic liquid.

[0116] Furthermore, the reaction time is selected from 1-3h.

[0117] As a further embodiment, the solvent is selected from one or more solvents of methanol, ethanol, isopropanol, ethyl acetate, and ethylene dichloride.

[0118] In a third aspect, the present invention provides a silicon-based negative electrode sheet, which includes the high-kinetic silicon-based negative electrode aqueous binder, a conductive agent, and a silicon-based active material described in the first aspect.

[0119] Furthermore, the silicon-based active material includes silicon granular materials, silicon-oxygen composite materials, and silicon-carbon composite materials; as some specific examples: the silicon-oxygen composite materials include one or more of silicon monoxide and silicon dioxide; the silicon-carbon composite materials include one or more of silicon / graphite composite materials, silicon / carbon nanotube composite materials, and silicon / graphene composite materials.

[0120] In a third aspect, the present invention provides a battery, comprising the silicon-based negative electrode sheet, positive electrode sheet, separator, and electrolyte described in the third aspect.

[0121] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0122] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0123] Example 1

[0124] Preparation of phenolic ionic liquids:

[0125] Pour 100 ml of ethanol into a 250 ml single-mouth bottle and start stirring. Add 5 g of caffeic acid and 5 g of choline into the single-mouth bottle in sequence. Protect with nitrogen atmosphere and react at 25±5 degrees for 2 hours. Then remove the solvent by rotary evaporator to obtain phenolic ionic liquid.

[0126] 13 g of acrylic acid, 4 g of 1% NaOH aqueous solution, and 5 g of acrylamide were added to a three-necked flask containing 250 mL of water. A nitrogen atmosphere was introduced during the entire reaction process, and the atmosphere flow rate was controlled at 500 mL / min. The temperature was increased until the temperature of the reaction system was maintained at 70°C. The entire system was heated in an oil bath. After the reaction temperature stabilized, it was kept at this temperature for 25 minutes.

[0127] Then, under the protection of nitrogen atmosphere, 5 g of acrylonitrile and 0.5 g of ammonium persulfate initiator were added to the above reaction system; the temperature was raised to maintain the temperature of the reaction system at 75° C. and the reaction was carried out for 3 hours to obtain the first slurry;

[0128] Take 15g of acrylic acid, 6g of acrylamide, 6g of acrylonitrile, 10g of 2-hydroxyethyl acrylate, 9g of 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate, and 7g of caffeic acid choline ionic liquid, mix them evenly, and add them dropwise into the flask containing the first slurry at a rate of 5 seconds per drop under the protection of a nitrogen atmosphere; keep warm for 7h, the reaction is completed, and a second slurry is formed.

[0129] Add 10% strong alkali aqueous solution dropwise to the second slurry until the pH value of the system is adjusted to 7-8.

[0130] Deionized water was continued to be added to the system with the pH value adjusted to 7-8 to dilute it to a solid content of 15%, thereby obtaining a high-kinetic silicon-based negative electrode aqueous binder.

[0131] Example 2

[0132] The specific steps and operation method are the same as those in Example 1, except that: 20 g of acrylic acid, 5 g of acrylamide, 8 g of acrylonitrile, 10 g of 2-hydroxyethyl acrylate, 9 g of 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate, and 7 g of caffeic acid choline ionic liquid are mixed evenly, and added dropwise to the flask containing the first slurry at a rate of 5 seconds per drop under the protection of a nitrogen atmosphere; the mixture is kept warm for 7 hours, the reaction is completed, and a second slurry is formed.

[0133] Example 3

[0134] The specific steps and operation methods are the same as those in Example 1, except that: 12 g of acrylic acid, 5 g of acrylamide, 7 g of acrylonitrile, 11 g of 2-hydroxyethyl acrylate, 8 g of 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate, and 5 g of caffeic acid choline ionic liquid are mixed evenly, and added dropwise to the flask containing the first slurry at a rate of 5 seconds per drop under the protection of a nitrogen atmosphere; the mixture is kept warm for 7 hours, the reaction is completed, and a second slurry is formed.

[0135] Example 4

[0136] The specific steps and operation methods are the same as those in Example 1, except that: caffeic acid betaine ionic liquid is prepared and used.

[0137] Example 5

[0138] The specific steps and operation methods are the same as those in Example 1, except that the zwitterionic liquid is selected from 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt.

[0139] Example 6

[0140] Pour 100 ml of ethanol into a 250 ml single-necked bottle and start stirring. Add 4 g of gallic acid and 4 g of triethylamine into the single-necked bottle in sequence. Protect with nitrogen atmosphere and react at 25±5 degrees for 2 hours. Then remove the solvent by rotary evaporator to obtain phenolic ionic liquid.

[0141] 13 g of methacrylic acid, 4 g of 1% NaOH aqueous solution, and 5 g of methacrylamide were added to a three-necked flask containing 250 mL of water; nitrogen atmosphere protection was required throughout the reaction process, and the atmosphere flow rate was controlled at 600 mL / min; the temperature was increased until the temperature of the reaction system was maintained at 75°C, and the entire system was heated in an oil bath. After the reaction temperature stabilized, it was kept at this temperature for 30 minutes.

[0142] Then, under the protection of nitrogen atmosphere, 5 g of α-methacrylonitrile and 0.5 g of ammonium persulfate initiator were added to the above reaction system; the temperature was raised to maintain the temperature of the reaction system at 75° C. and the reaction was carried out for 3 hours to obtain a first slurry;

[0143] Take 15g of methacrylic acid, 6g of methacrylamide, 6g of α-methacrylonitrile, 10g of n-butyl acrylate, 9g of 4-[[2-(methacryloyloxy)ethyl]dimethylammonium]butane-1-sulfonate, and 7g of gallic acid-triethylamine ionic liquid, mix them evenly, and add them dropwise into the flask containing the first slurry at a rate of 5 seconds per drop under nitrogen atmosphere; keep warm for 7h, the reaction is completed, and a second slurry is formed.

[0144] Add 10% strong alkali aqueous solution dropwise to the second slurry until the pH value of the system is adjusted to 7-8.

[0145] Deionized water was continuously added to the system with the pH value adjusted to 7-8 to dilute the system to a solid content of 18%, thereby obtaining a high-kinetic silicon-based negative electrode aqueous binder.

[0146] Example 7

[0147] The specific steps and operation methods are the same as those in Example 1, except that: 100 ml of ethanol is poured into a 250 ml single-mouth bottle, stirring is started, 5 g of caffeic acid and 7 g of choline are added to the single-mouth bottle in sequence, a nitrogen atmosphere is provided, and the reaction is carried out at 25±5 degrees for 2 hours, and then the solvent is removed by a rotary evaporator to obtain a phenolic ionic liquid.

[0148] Comparative Example 1

[0149] The specific steps and operation methods are the same as those in Example 1, except that: 20 g of acrylic acid, 3 g of acrylamide, 3 g of acrylonitrile, 5 g of 2-hydroxyethyl acrylate, 3 g of 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate, and 3 g of caffeic acid choline ionic liquid are mixed evenly, and added dropwise to the flask containing the first slurry at a rate of 5 seconds per drop under the protection of a nitrogen atmosphere; the mixture is kept warm for 7 hours, the reaction is completed, and a second slurry is formed.

[0150] Comparative Example 2

[0151] The specific steps and operation methods are the same as those in Example 1, except that:

[0152] Take 28g acrylic acid, 11g acrylamide, 11g acrylonitrile, 10g 2-hydroxyethyl acrylate, 9g 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate, 7g caffeic acid choline ionic liquid, and 0.5g ammonium persulfate initiator, mix them evenly, and add them dropwise into a three-necked flask containing 250mL of water at a rate of 5 seconds per drop under the protection of nitrogen atmosphere; nitrogen atmosphere protection is required throughout the reaction process, and the atmosphere flow rate is controlled at 500mL / min; the temperature is increased until the temperature of the reaction system is maintained at 75°C, and the whole system is kept warm for 7h under oil bath heating, and the reaction is completed.

[0153] Comparative Example 3

[0154] The specific steps and operation method are the same as those in Example 1, except that no 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate and caffeic acid choline ionic liquid are added.

[0155] Comparative Example 4

[0156] The specific steps and operation method are the same as those in Example 1, except that 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate is not added.

[0157] Comparative Example 5

[0158] The specific steps and operation method are the same as those in Example 1, except that no caffeic acid choline ionic liquid is added.

[0159] Comparative Example 6

[0160] The specific steps and operation methods are the same as those in Example 1, except that: 100 ml of ethanol is poured into a 250 ml single-mouth bottle, stirring is started, 5 g of caffeic acid and 15 g of choline are added to the single-mouth bottle in sequence, a nitrogen atmosphere is protected, the reaction is carried out at 25±5 degrees for 2 hours, and then the solvent is removed by a rotary evaporator to obtain a phenolic ionic liquid.

[0161] Specific test methods and conditions:

[0162] (1) Battery preparation: Nano silicon + conductive carbon black (SP) + graphite + comparative products of various embodiments were mixed in a mass ratio of 70:5:15:10 and coated on the current collector copper foil, and then dried, cold pressed, and cut to obtain the negative electrode sheet; nickel cobalt manganese oxide (NCM811) + conductive carbon black (SP) + polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1 and coated on the current collector aluminum foil, and then dried, cold pressed, and cut to obtain the positive electrode sheet; 25 μm thick PP was used as a separator; ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:1, and LiPF6 was added to the mixed solution to obtain a solution with a concentration of 1 mol / L as the electrolyte. The positive electrode sheet, the separator, and the negative electrode sheet were stacked in sequence, wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, injected with electrolyte and sealed, and assembled soft-pack batteries were obtained after formation.

[0163] (2) Film swelling rate test: Pour the adhesive synthesized in the comparative example of each embodiment into a mold of a certain volume, place it in an oven at a constant temperature of 45°C and dry it for 48 hours to obtain a water-free film of a certain thickness. Take a film of appropriate size and soak it in a lithium salt electrolyte without additives (note that the electrolyte needs to be kept in an environment with controlled humidity, and the film soaking environment of the present invention is a glove box), seal it and place it in a constant temperature oven at 75°C for storage, record the mass change of the film after 9 days, and the increase relative to the initial mass of the film divided by the initial mass of the film is the swelling rate.

[0164] (3) Peel force cohesion test: The peel force test is used to evaluate the bonding strength between the active material coating on the battery electrode and the current collector (copper foil). During the test, a specimen of specified size is cut from the electrode, one end of which is fixed on a fixture, and the other end is peeled off from the current collector at a constant speed (usually 300 mm / min) at an angle of 90°, and the maximum peel force is recorded. The cohesion test checks the bonding strength of the active material coating itself to prevent the coating from delamination or falling off during use. The test method is to fix both ends of the specimen on a fixture and stretch it at a constant speed until the coating breaks, and record the required pulling force to evaluate the stability of the coating.

[0165] (4) Constant capacity rebound test: The battery is kept in a constant temperature box at 25°C for full charge, with the voltage range set to 2.5-4.2V and the current set to 0.5A. After full charge, the battery is disassembled and the thickness of the silicon-based negative electrode sheet at different locations is tested using a micrometer, and the average value is taken. The increase in the thickness of the electrode sheet after full charge relative to the electrode sheet after rolling is the full charge rebound.

[0166] (5) Constant capacity extension length / width test: The battery is kept in a constant temperature box at 25°C for full charge, with the voltage range set to 2.5-4.2V and the current set to 0.5A. After full charge, the battery is disassembled and the length and width of the silicon-based negative electrode sheet are measured with a film ruler. The increase in the length / width of the silicon-based negative electrode sheet during the battery preparation stage is the constant capacity extension length / width.

[0167] (6) Impedance test: The battery is in a stable state, that is, the battery is fully charged or discharged and reaches the specified state of charge (50% SOC). The test should be completed in a constant temperature environment of 25°C to avoid the influence of temperature fluctuations on the results. In addition, in order to ensure the accuracy of the test results, it is necessary to select a suitable frequency range and AC signal amplitude. Therefore, the frequency range is set to 0.001-100000Hz, the AC amplitude is 5mV, and the battery is kept stationary during the entire test.

[0168] (7) Cycle performance test: The battery was kept in a constant temperature box at 25°C for battery cycling, with the voltage range set to 2.5-4.2V and the current set to 0.5A. The number of cycles when the battery capacity retention rate dropped to 80% was recorded, and the average coulombic efficiency of the battery was calculated.

[0169] (8) Battery expansion rate: At room temperature of 25°C, use a thickness gauge to measure the initial thickness of the battery. After the battery cycle is completed, use a thickness gauge to measure the final thickness of the battery. The final thickness minus the initial thickness divided by the initial thickness is the battery expansion rate.

[0170] The test results of the embodiments and comparative examples are shown in Table 1 and Table 2.

[0171] Table 1

[0172]

[0173] Table 2

[0174]

[0175]

[0176] It can be seen from the data of Examples 1-7, Comparative Examples 1-6 and Table 1 that the aqueous binder prepared in Examples 1-7 has high adhesion and flexibility, and it can also be seen from the data of Table 2 that the aqueous binder of the present invention has a low swelling rate and good electrochemical performance and cycle stability in silicon-based negative electrode battery applications.

[0177] By comparing Examples 1-7 with Comparative Example 1, it can be seen that a suitable component ratio in the aqueous binder is more conducive to the preparation of an aqueous binder with high dynamics; compared with Examples 1-7; the relative content of acrylic ester monomers, zwitterionic monomers, and phenolic ionic liquids in the aqueous binder in Comparative Example 1 is relatively small, resulting in the aqueous binder prepared in Comparative Example 1 having a higher cohesive force, but poor peeling force, constant volume rebound, and elongation; this is because the ester group present in the acrylic ester monomer can effectively alleviate the excessive rigidity that may be caused by the strong hydrogen bonding effect in the acrylic acid system, resulting in the breakage of the cross-linked network of the binder; affecting its flexibility, thereby failing to effectively inhibit the volume expansion of the silicon-based negative electrode, resulting in a higher swelling rate, and poor electrochemical performance and cycle stability.

[0178] In Comparative Example 2, different components of binders are directly reacted to prepare an aqueous binder. Compared with Examples 1-7 in which a primary cross-linked network is first constructed, the aqueous binder prepared in Comparative Example 2 has higher impedance and cohesion, while higher elongation, constant volume rebound rate and swelling rate. This is because direct cross-linking polymerization is not conducive to forming a uniform cross-linked network. The growth distribution of the three-dimensional cross-linked network structure cannot be effectively regulated, and thus, when the silicon-based negative electrode material is cycled, stress cannot be effectively absorbed and expansion cannot be inhibited. This results in the binder being more brittle, easy to fall off during the cycle, and having lower peeling force and cycle stability.

[0179] It can be seen from the data in Tables 1 and 2 that the binder components of Examples 1-7 are conducive to the best synergistic effect, and the silicon-based negative electrode material thereof has a higher surface density and a stronger peeling force; a water-based binder with high viscosity is obtained; at the same time, the binder prepared in Examples 1-7 has a lower volume rebound and elongation, and a moderate range of cohesive force, indicating that the water-based binder prepared in Examples 1-7 also has higher flexibility and can effectively alleviate the volume expansion of the silicon-based negative electrode material; thereby having higher electrochemical stability.

[0180] Compared with Examples 1-7, when no zwitterionic monomers and phenolic ionic liquids are added to Comparative Examples 3, 4, and 5, or when only one of them is added, we can see that the performance of preparing water-based binders is relatively low. This is because the presence of zwitterionic monomers and phenolic ionic liquids can further improve the ionic conductivity of the water-based binder; at the same time, the cohesive force and peeling force in the system are balanced to obtain a structure with good flexibility, and the volume expansion of the silicon-based negative electrode is always prevented. When Comparative Example 5 chooses to add only zwitterionic monomers, although it can improve the ionic conductivity of the binder to a certain extent; but the improvement effect is limited; and the coordinated use with phenolic ionic liquids helps to enhance the fluidity of the binder system and obtain a uniform three-dimensional network structure. Similarly, in Comparative Example 4, the synergistic effect of zwitterions is lacking, and the impedance and coulomb efficiency of its preparation of water-based binders are also low; this is because the zwitterionic monomers can not only form a strong interaction with the acrylic system, participate in the cross-linking polymerization reaction, but also connect the interface compatibility between the phenolic ionic liquid and the acrylic system; it is convenient to prepare a water-based binder with good dynamic properties, high flexibility and high viscosity.

[0181] It can be seen from Examples 1-7 and Comparative Example 6 that when preparing phenolic ionic liquids, the amount of alkaline components added in Comparative Example 6 is too much relative to that used in this example; it will cause the failure to form a stable amide bond when condensing with phenolic acidic components, and will also cause other side reactions; the ratio of anions and cations is unbalanced. This imbalance may affect the conductivity of the ionic liquid; it is not conducive to the preparation of an aqueous binder with higher kinetics. It can also be seen from the data in Table 2 that its impedance and coulombic efficiency are poor, and the battery cycle performance is also low. Examples 1-7 use a suitable range of mass ratios to prepare phenolic ionic liquids, which is conducive to obtaining an aqueous binder with high flexibility and good electrochemical properties.

[0182] It can be seen from Examples 1-4 and 5-7 that the binder components and types within the optimized range are more conducive to achieving a balance between the binder's dynamic properties and flexibility and bonding strength; have lower impedance and obtain a more uniform three-dimensional cross-linked network; not only have a lower swelling rate and improve battery cycle stability, but also have a more direct and rapid ion transmission path, promote ion conduction, and improve the battery's dynamic performance.

[0183] pass Figure 1It can be seen that the binder prepared in Example 1 of the present invention is applied to the silicon-based negative electrode to prepare the electrode sheet. The negative electrode binder has good film-forming properties and is very evenly distributed in the negative electrode. There is no binder agglomeration phenomenon, and it can efficiently bond the components of the negative electrode, and can effectively prevent the active material from falling off the current collector during the charge and discharge process, thereby improving the mechanical stability of the electrode. At the same time, the binder is evenly distributed in the negative electrode material, which can ensure good contact between the active material particles, which is beneficial to the efficient transmission of electrons and ions in the negative electrode, thereby improving the stability of the battery cycle.

[0184] pass Figure 2 It can be seen that the binder in comparative example 1 of the present invention is applied to the silicon-based negative electrode to prepare the electrode sheet. The film-forming property of the negative electrode binder is poor, the distribution in the negative electrode is uneven, the agglomeration phenomenon is obvious, and a continuous and dense film cannot be formed, resulting in poor integrity of the electrode structure. Therefore, the cycle life of the battery is short and the performance declines significantly.

[0185] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-kinetic silicon-based negative electrode aqueous binder; wherein, The raw materials of the water-based binder include five parts: By weight, 20-35 parts of acrylic monomer; 15 to 30 parts of acrylic acid derivative monomer; 8 to 18 parts of acrylic ester monomer; 5 to 15 parts of zwitterionic monomer; 4 to 10 parts of phenolic ionic liquid; Wherein, the acrylic acid derivative monomer has a nitrogen-containing hydrogen bond acceptor derivative group.

2. The high-kinetic silicon-based negative electrode aqueous binder according to claim 1, characterized in that: The raw materials of the high-dynamic silicon-based negative electrode aqueous binder also include, by weight, 0.5-1 parts of initiator and 200-450 parts of water solvent.

3. The high-kinetic silicon-based negative electrode aqueous binder according to claim 1, characterized in that: The acrylic monomer includes one or more of acrylic acid, alkyl acrylic acid, acrylate, and alkyl acrylate; The acrylic acid derivative monomer is selected from acrylamide monomers and acrylonitrile monomers; wherein the mass ratio of acrylamide monomers to acrylonitrile monomers is in the range of 1:(0.5-1.5); Further, the acrylamide monomers include one or more of acrylamide, methacrylamide, N-methylacrylamide, N-ethylacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, N-hydroxypropylacrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide; the acrylonitrile monomers include one or more of acrylonitrile, α-methacrylonitrile and α-ethylacrylonitrile; Furthermore, the salts of the acrylate and alkyl acrylate can be selected from lithium salt, sodium salt and potassium salt; Furthermore, the alkyl group is selected from one or more of methyl, ethyl and propyl.

4. The high-kinetic silicon-based negative electrode aqueous binder according to claim 1, characterized in that: The acrylic ester monomers include one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, lauryl acrylate, vinyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate; The zwitterionic monomers include one or more zwitterionic organic acid ester ionic monomers selected from 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate; one or more zwitterionic organic salt ionic monomers selected from 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, 3-[bis[2-(methacryloyloxy)ethyl](methyl)ammonium]-1-propane sulfonate, (3-(methacryloylamino)propyl)dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 3-[[2-(acryloyloxy)ethyl]dimethylammonium]propane-1-sulfonate, 4-[[2-(methacryloyloxy)ethyl]dimethylammonium]butane-1-sulfonate, and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate; Furthermore, the zwitterionic monomer is preferably selected from zwitterionic organic acid ester ionic monomers.

5. The high-kinetic silicon-based negative electrode aqueous binder according to claim 1, characterized in that: The phenolic ionic liquid is a product obtained by an acid-base neutralization reaction between a phenolic acid component and an alkaline component; the mass ratio of the phenolic acid component to the alkaline component is selected from 1: (0.7-1.5); Further, the phenolic acidic component includes one or more of gallic acid, protocatechuic acid, vanillic acid, syringic acid, gentisic acid, caffeic acid, ferulic acid, p-coumaric acid, sinapic acid, rosmarinic acid, p-hydroxybenzoic acid and salicylic acid; the alkaline component includes one or more of choline, betaine, ethylenediamine and triethylamine; Furthermore, the phenolic acid component is preferably selected from phenolic acid components having a substituent group (-C=C-CO-) connected to a carbon-carbon unsaturated bond on the carbonyl carbon; including one or more of caffeic acid, ferulic acid, sinapinic acid, and rosmarinic acid; Furthermore, the alkaline component is preferably selected from alkaline components containing quaternary ammonium groups, including one or more of choline and betaine.

6. The high-kinetic silicon-based negative electrode aqueous binder according to claim 1, characterized in that: The raw materials of the water-based binder are preferably: 25 to 35 parts of acrylic monomers; 15 to 23 parts of acrylic acid derivative monomer; 10 to 13 parts of acrylic ester monomer; 7 to 10 parts of zwitterionic monomer; 4 to 7 parts of phenolic ionic liquid; Wherein, the acrylic acid derivative monomer has a nitrogen-containing hydrogen bond acceptor derivative group; Further, the nitrogen-containing hydrogen bond acceptor derivative group includes one or more of an amino group, an amide group, a carbon-nitrogen double bond (C=N), and a carbon-nitrogen triple bond (C≡N); Furthermore, the raw materials of the water-based binder are preferably acrylic acid monomers, acrylamide monomers, acrylonitrile monomers, acrylic ester monomers, amphoteric organic acid ester ion monomers, and phenolic ionic liquids.

7. A method for preparing a high-kinetic silicon-based negative electrode aqueous binder, characterized in that: The preparation method is used to prepare the high-kinetic silicon-based negative electrode aqueous binder according to any one of claims 1 to 6; the steps include: S1: heating the acrylic acid monomer, acrylic acid derivative monomer, alkaline solution and aqueous solution to 50-80° C. under an inert atmosphere; keeping the temperature for 15-35 minutes; S2: Adding acrylic acid derivative monomer to S1 again; adding initiator and keeping warm for 2-4 hours to obtain the first slurry; adjusting the temperature range to 65-90°C; S3: When the temperature reaches the temperature range of 65-90° C. described in S2, a mixture of acrylic acid monomers, acrylic acid derivative monomers, acrylic ester monomers, zwitterionic monomers, and phenolic ionic liquids is added to the first slurry described in S2; after the addition is completed, the temperature is kept for 7-13 hours to obtain a second slurry; S4: adding a strong alkaline aqueous solution to the second slurry in S3; adjusting the pH value to 7-8; and diluting with water to obtain a high-kinetic silicon-based negative electrode aqueous binder; Furthermore, the acrylic acid derivative monomer in S1 is preferably selected from acrylamide monomers; the acrylic acid derivative monomer in S2 is preferably selected from acrylonitrile monomers; the acrylic acid derivative monomer in S3 is preferably selected from acrylamide monomers and acrylonitrile monomers; wherein the acrylic acid derivative monomer has a nitrogen-containing hydrogen bond acceptor derivative group; Further, the solid content of the high-kinetic silicon-based negative electrode aqueous binder is in the range of 10-30%; Further, the addition rate in S3 is in the range of 3-6 seconds per drop; Further, the initiator in S2 is selected from one or more of an inorganic peroxide initiator, an organic peroxide initiator, and an azo initiator; as some specific examples: the inorganic peroxide initiator is selected from one or more of ammonium persulfate, potassium persulfate, and sodium persulfate; the organic peroxide initiator is selected from one or more of benzoyl peroxide, di-tert-butyl peroxide, and methyl ethyl ketone peroxide; the azo initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate; Furthermore, the inert atmosphere in S1 is selected from one or more of a nitrogen atmosphere and a helium atmosphere; Further, the atmosphere flow rate of the inert atmosphere in S1 is selected from 500-1000 mL / min; Furthermore, the type of the alkaline solution in S1 is selected from one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide; the concentration of the alkaline solution is in the range of 1-10%; Furthermore, in S4, the type of the strong alkali aqueous solution is selected from one or more of a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, and a lithium hydroxide aqueous solution; and the concentration range of the strong alkali aqueous solution is 10-20%.

8. The method for preparing a high-kinetic silicon-based negative electrode aqueous binder according to claim 7, characterized in that: The preparation method of the phenolic ionic liquid in S3 comprises: adding a phenolic acid component and a basic component to a solvent according to a mass ratio; after the reaction is completed under an inert atmosphere, removing the solvent to obtain a phenolic ionic liquid; Further, the reaction time is selected from 1-3h; Furthermore, the solvent is selected from one or more solvents of methanol, ethanol, isopropanol, ethyl acetate and ethylene dichloride.

9. A silicon-based negative electrode sheet, characterized in that: The silicon-based negative electrode sheet comprises the high-kinetic silicon-based negative electrode aqueous binder, a conductive agent, and a silicon-based active material according to any one of claims 1 to 8; Furthermore, the silicon-based active material includes silicon granular materials, silicon-oxygen composite materials, and silicon-carbon composite materials; as some specific examples: the silicon-oxygen composite materials include one or more of silicon monoxide and silicon dioxide; the silicon-carbon composite materials include one or more of silicon / graphite composite materials, silicon / carbon nanotube composite materials, and silicon / graphene composite materials.

10. A battery, characterized in that: The battery comprises the silicon-based negative electrode sheet, positive electrode sheet, separator and electrolyte as described in claim 9.

Citation Information

Cited By

  • Multifunctional amide structure monomer-based silicon-based negative electrode binder and application thereof in lithium / sodium battery

    CN121555117A

  • Multifunctional amide structure monomer-based silicon-based negative electrode binder and application thereof in lithium / sodium batteries

    CN122542164A